The Role of Transformational Leadership, Team Effectiveness and Well-Being in Predicting Employee Innovation Behavior in the Culinary Sector - Musyrifi, Salman Al; Lailan, Mohamad Rizki; Sadewo, Akbar; Siddiq, Dedi Muhammad; Setapa, Mariam (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to explore the relationship of transformational leadership roles, team effectiveness, and well-being with employee innovation behavior in the context of the culinary sector marked as city branding product. This study uses quantitative methods by collecting data through the distribution of questionnaires to employees of culinary sector businesses where the culinary includes city branding products. The results of the data analysis showed that transformational leadership and team effectiveness had a positive relationship with employee innovation behavior, while employee well-being has no relationship with employee innovation behavior. These findings provide important insights for managers and leaders in the culinary sector in understanding the factors influencing employee innovative behaviour in the organizations producing products marked as an icon of the city.